2021
DOI: 10.3389/fonc.2020.607235
|View full text |Cite
|
Sign up to set email alerts
|

An Approach Based on Mammographic Imaging and Radiomics for Distinguishing Male Benign and Malignant Lesions: A Preliminary Study

Abstract: PurposeTo develop and validate an imaging-radiomics model for the diagnosis of male benign and malignant breast lesions.MethodsNinety male patients who underwent preoperative mammography from January 2011 to December 2018 were enrolled in this study (63 in the training cohort and 27 in the validation cohort). The region of interest was segmented into a mediolateral oblique view, and 104 radiomics features were extracted. The minimum redundancy and maximum relevance (mRMR) and the least absolute shrinkage and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In this study, we developed the radiomics models for diagnosis of breast cancer using DCE-MRI alone, mammography alone, and the combined MRI and mammography. While quite a few studies have reported the radiomics models developed using MRI (23,24,34) or mammography (19)(20)(21)(22), the combined analysis was rarely reported (35). We further investigated the complementary role of MRI and mammography features in diagnostic sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we developed the radiomics models for diagnosis of breast cancer using DCE-MRI alone, mammography alone, and the combined MRI and mammography. While quite a few studies have reported the radiomics models developed using MRI (23,24,34) or mammography (19)(20)(21)(22), the combined analysis was rarely reported (35). We further investigated the complementary role of MRI and mammography features in diagnostic sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…MRI radiomics was shown to provide better discrimination than conventional parameters for the diagnosis of breast cancer (23,24). Mammography radiomics analysis has also been performed in several diagnostic studies (19)(20)(21)(22). However, since the patient cohort is different, the diagnostic accuracy will be highly dependent on the inclusion/exclusion criteria, and not directly comparable among studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations